The Growth-Environment Trade-off: Horizontal vs Vertical Innovations - André Grimaud; Francesco Ricci (Fondazione Eni Enrico Mattei (FEEM), 1999)
This paper explores the trade-off between economic growth and environmental quality along two paradigms of endogenous growth theory: variety expansion (HIP) and quality improvements (VIP). We compare the policies that match the decentralised economies' paths with the optimal "strong sustainable" growth path, characterised by growth in consumption and improvements in environmental quality. Three policy tools are employed: subsidies to monopolists and R&D, and taxes on emissions. The latter is increasing at the optimum, to keep the weight of tax revenues over output constant. All policy tools equal, the growth rate is higher in the VIP than in the HIP. The optimal subsidy to R&D is therefore greater and the cumulative loss in output smaller under HIP than the VIP.
Keywords: O41; Q20; 330; Pollution; Endogenous Growth; Sustainable Development; Neue Wachstumstheorie; Nachhaltige Entwicklung; Innovation; Gleichgewichtiges Wachstum; Umweltpolitik; Theorie